Label‐free biomarkers of human embryonic stem cell differentiation to hepatocytes. Issue 6 (23rd May 2016) - Tsikritsis, Dimitrios; Shi, Hu; Wang, Yuan; Velugotla, Srinivas; Sršeň, Vlastimil; Elfick, Alistair; Downes, Andrew
Abstract: Four different label‐free, minimally invasive, live single cell analysis techniques were applied in a quantitative comparison, to characterize embryonic stem cells and the hepatocytes into which they were differentiated. Atomic force microscopy measures the cell's mechanical properties, Raman spectroscopy measures its chemical properties, and dielectrophoresis measures the membrane's capacitance. They were able to assign cell type of individual cells with accuracies of 91% (atomic force microscopy), 95.5% (Raman spectroscopy), and 72% (dielectrophoresis). In addition, stimulated Raman scattering (SRS) microscopy was able to easily identify hepatocytes in images by the presence of lipid droplets. These techniques, used either independently or in combination, offer label‐free methods to study individual living cells. Although these minimally invasive biomarkers can be applied to sense phenotypical or environmental changes to cells, these techniques have most potential in human stem cell therapies where the use of traditional biomarkers is best avoided. Destructive assays consume valuable stem cells and do not characterize the cells which go on to be used in therapies; whereas immunolabeling risks altering cell behavior. It was suggested how these four minimally invasive methods could be applied to cell culture, and how they could in future be combined into one microfluidic chip for cell sorting. © 2016 International Society for Advancement of Cytometry